1200. Molecular Epidemiology of Cephalosporinases and Extended Spectrum β-Lactamases (ESBLs) in Proteus mirabilis Isolates From Croatia: Following the Spread of Resistance Determinants Between Long-Term Care Facilities and the Community. (26th November 2018) - Mestrovic, Tomislav; Lukic-Grlic, Amarela; Bogdan, Maja; Bandic-Pavlovic, Daniela; Cavric, Gordana; Drenjancevic, Domagoj; Sreter, Katherina Bernardette; Bencic, Ana; Sardelic, Sanda; Bedenic, Branka
Abstract: Background: Previous studies on P. mirabilis strains isolated from Croatian healthcare institutions revealed the predominance of TEM-52 extended spectrum β-lactamase (ESBL), as well as the emergence of plasmid AmpC β-lactamases. Our aim was to molecularly characterize cefalosporinases in P. mirabilis isolates from long-term care facilities (LTCFs) and to compare their resistance profile and dynamics with community isolates. Methods: From a total of 3, 321 P. mirabilis isolates collected from two LCTFs and from outpatients between 2015 and 2017, 1.23% of them were resistant to third generation of cephalosporins. Antimicrobial sensitivity was tested by broth microdilution method. ESBLs and plasmid-mediated AmpC β-lactamases were detected with phenotypic inhibitor-based tests and polymerase chain reaction (PCR). Antibiotic resistance dissemination and genetic context of bla genes were interrogated by conjugal mating and PCR mapping, respectively. Plasmids were characterized by conjugation and transformation experiments, as well as PCR-based replicon typing. Results: High-level of resistance to amoxicillin, co-amoxiclav, first, second and third generation of cephalosporins was found in all isolates. Three isolates tested positive in inhibitor-based test with clavulanic acid, and 38 both in Hodge test and combined disk test with phenylboronic acid, indicating the production of ESBLs and plasmid-mediated AmpC β-lactamases, respectively. Two ESBL-positive organisms yielded amplicons with primers for CTX-M β-lactamase of group 1 and one for TEM. All AmpC-positive organisms were identified by PCR as CMY (with an additional TEM). Insert sequence IS Ecp-1 was found upstream of bla CMY i bla CTX-M genes. CTX-M positive strains harbored IncK plasmid, whereas AmpC-positive strains were negative for known plasmid types. This is also a first description of P. mirabilis harboring CTX-M-15 β-lactamase in Croatia. Conclusion: Our study showed the persistence of CMY β-lactamases in one LTCF, but also the dissemination of characteristic resistance determinants to another LTCF and the community. Similar to some other studies, there was a clear trend of cephalosporinase dynamic switch from TEM variants to CMY and CTX-M, with impending consequences for treatment decisions. Disclosures: All authors: No reported disclosures.